2014
DOI: 10.1038/gim.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Population-based estimates of the prevalence of FMR1 expansion mutations in women with early menopause and primary ovarian insufficiency

Abstract: Purpose:Primary ovarian insufficiency before the age of 40 years affects 1% of the female population and is characterized by permanent cessation of menstruation. Genetic causes include FMR1 expansion mutations. Previous studies have estimated mutation prevalence in clinical referrals for primary ovarian insufficiency, but these are likely to be biased as compared with cases in the general population. The prevalence of FMR1 expansion mutations in early menopause (between the ages of 40 and 45 years) has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 24 publications
(34 reference statements)
2
61
1
3
Order By: Relevance
“…POI ("POF1" in OMIM 311360) has been consistently associated with women who have the "premutation" state of the Xq27.1 FMR1 gene (i.e., between 55 and 200 tandem copies of the CGG trinucleotide repeat in the gene). In two studies [67,68], 3% of sporadic and 10-13% of familial POI patients carried FRAXA premutations; in a more extensive follow-up, Murray et al [69] found the permutation in 0.7% of 2,000 women with early menopause and in 2% of women with POI (an odds ratio for POI of 5.4 compared with 0.4% in controls). FMR1 has a primary effect in the brain [70], but is also implicated in the DNA damage response [71], and could thereby have a determinative effect on chromosome dynamics and oocyte stability.…”
Section: X-autosomal Translocations and Chromosomal Changesmentioning
confidence: 95%
“…POI ("POF1" in OMIM 311360) has been consistently associated with women who have the "premutation" state of the Xq27.1 FMR1 gene (i.e., between 55 and 200 tandem copies of the CGG trinucleotide repeat in the gene). In two studies [67,68], 3% of sporadic and 10-13% of familial POI patients carried FRAXA premutations; in a more extensive follow-up, Murray et al [69] found the permutation in 0.7% of 2,000 women with early menopause and in 2% of women with POI (an odds ratio for POI of 5.4 compared with 0.4% in controls). FMR1 has a primary effect in the brain [70], but is also implicated in the DNA damage response [71], and could thereby have a determinative effect on chromosome dynamics and oocyte stability.…”
Section: X-autosomal Translocations and Chromosomal Changesmentioning
confidence: 95%
“…This definition has been used elsewhere to define a normal age at menopause. 30 In addition, women were excluded: if they had ever taken fertility medications, if they had ever had a period of 12 months when they could not become pregnant despite regular sexual activity without contraception, if they had never been pregnant, or if the answer to any of these 3 questions was missing.…”
Section: Participation In This Fragile X Analysismentioning
confidence: 99%
“…Both Pastore and Barosoain et al reported that women with low (or diminished) ovarian reserve were more likely to have ≥35 CGG repeats as compared to their comparison groups (p=0.0003 and p<0.05) [9,26]. Where the interpretation of the aforementioned [9,24] [25].…”
Section: Discussionmentioning
confidence: 98%
“…Karimov et al analyzed 1056 patients (535 cases with low ovarian reserve and 521 infertile controls [unrelated to ovarian reserve] and oocyte donors) and reported that in addition to PM carriers, women who carried an intermediate ranged mutation (45-54 repeats) exhibited a higher prevalence of DOR [7]. Thereafter, four studies examined repeat lengths ranging from 35 to 54 and ovarian reserve or age at menopause [9,[23][24][25]. Both Pastore and Barosoain et al reported that women with low (or diminished) ovarian reserve were more likely to have ≥35 CGG repeats as compared to their comparison groups (p=0.0003 and p<0.05) [9,26].…”
Section: Discussionmentioning
confidence: 99%